San Francisco's urban transformations since the 1980s - Richard Hu (University of California, Institute of Urban and Regional Development (IURD), 2009)
This paper examines San Francisco's urban development transformations in the post-1980 decades. The transformations are examined through two spectrums: functional concentration and economic base. Through the variables of employment by land use and floor area by land use, the functional concentration analysis identifies the changes of the urban functions concentrated in San Francisco. The economic base analysis uses the data of employment by industry to find out San Francisco's economic transformations and economic drivers with reference to the entire Bay Area as a metropolitan region.
Keywords: 330